2010
DOI: 10.1590/s0102-311x2010000700014
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative analysis of the diet of a probabilistic sample of schoolchildren from Florianópolis, Santa Catarina State, Brazil, using the Previous Day Food Questionnaire

Abstract: A qualitative evaluation of the diet of a probabilistic sample of 7-10 year old schoolchildren (n = 1,232) from Florianópolis (southern Brazil) was carried out by analyzing compliance with recommendations from the Brazilian Food Guidelines. The strengths and limitations of the Previous Day Food Questionnaire (PDFQ) are also presented. Frequencies of intake were defined as how many times per day the food group was reported on the PDFQ. The percentages of schoolchildren who met the minimum recommendations and wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
1
20

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 23 publications
(28 reference statements)
4
23
1
20
Order By: Relevance
“…Investigations on the consumption of fruits and vegetables in Brazil have shown that only 15% of students in the city of Florianópolis (SC),17 6.5% in the city of Caruaru (PE),18 5.3% in the city of Pelotas (RS)19 and 2.7% in the state of Santa Catarina20 consume the recommended amount of fruits and vegetables. In Pernambuco,21 one out of three adolescents does not consume or consumes fruits and vegetables at least once per day and 62.9% of them are daily exposed to excessive consumption of soft drinks.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations on the consumption of fruits and vegetables in Brazil have shown that only 15% of students in the city of Florianópolis (SC),17 6.5% in the city of Caruaru (PE),18 5.3% in the city of Pelotas (RS)19 and 2.7% in the state of Santa Catarina20 consume the recommended amount of fruits and vegetables. In Pernambuco,21 one out of three adolescents does not consume or consumes fruits and vegetables at least once per day and 62.9% of them are daily exposed to excessive consumption of soft drinks.…”
Section: Discussionmentioning
confidence: 99%
“…Criteria for inclusion of processed foods in the study We selected processed foods that, based on a review of the literature (11)(12)(13)(29)(30)(31)(32)(33)(34) , met the following criteria: (i) they were present in the diets of Brazilian children and adolescents according to studies and/or official documents that assessed dietary intake in these age groups; and (ii) they were characterized as snacks or snack ingredients.…”
Section: Data Collectionmentioning
confidence: 99%
“…In addition, a search was done on official Brazilian government agency websites to research official documents reporting the foods consumed by children and adolescents. We selected references whose results included lists of foods consumed by Brazilian children and adolescents, totalling eight studies and two official documents (11)(12)(13)(29)(30)(31)(32)(33)(34) .…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The instrument containing 38 closed questions was constructed by adapting the questionnaire proposed by the team responsible for the project "Study of Childhood Obesity in Florianópolis" 18 . The adjustments made included the review of question wording, which went from a self-report format to face-to-face interview, and the inclusion of a section related to the physical activity measurement of the instrument proposed by Burdette et al 19 .…”
Section: Schoolmentioning
confidence: 99%